Analysis Of Regional Tax Revenue Contribution To Local Own-Source Revenue And Projection In Bontang City - Hermansyah, Hermansyah; Roy, Juliansyah; Suharto, Rahcmad Budi (CV. Publikasi Indonesia, 2025)
This study aims to analyze the contribution of regional tax revenue to Local Own-Source Revenue (PAD) in Bontang City and to project its future potential based on historical data. The research employs a descriptive quantitative approach using secondary data obtained from government institutions such as the Regional Revenue Agency (Bapenda), the Regional Financial and Asset Management Agency (BPKAD), and the Central Bureau of Statistics (BPS). The data collected from 2019 to 2024 were analyzed using contribution analysis and linear trend projection (least square method) to evaluate the role of regional taxes in supporting fiscal independence. The findings indicate that although Bontang City has several tax bases—such as hotel tax, restaurant tax, entertainment tax, and land and building tax (PBB-P2)—their contribution to PAD has fluctuated and has not reached an optimal level. The projection results show the potential for increasing tax contributions in the coming years, provided that the local government implements more effective intensification and extensification strategies. This study provides theoretical contributions to the development of public finance literature and offers practical implications for policymakers in optimizing local tax revenues to strengthen fiscal independence and improve public services in the era of decentralization.